The impact of the project-based learning (PBL) on the motivation of first-year students at Universitas Negeri Medan - Hasan, Hanapi; Jalinus, Nizwardi; Abdullah, Rijal; Ambiyar, Ambiyar; Fadhilah, Fadhilah; Putri, Tansa Trisna Astono (Journal of Computer Science, Information Technology and Telecommunication Engineering, 2024)
The goal of this study is to look at the effect of new learning approaches like project based learning (PBL) on the enthusiasm for studying of undergraduates at Universitas Negeri Medan. In the quasi-experimental design, the Times-Series Design with Control Group was used. The one-way ANOVA test was used to evaluate the data. The results demonstrated that the pretest and posttest motivation questionnaires in the control and experimental classes of the PBL paradigm differed. The mean of pretest motivation score for the experiment group was 3.50, by input score that varied from 3.00-3.97 and a standard deviation of 0.58. The mean of posttest motivation score for the experiment group was 3.83, by a score that ranged from 3.03-4.00 and a standard deviation of 0.61.